Genotype and phenotype spectrum of 10 children with STXBP1 gene-related encephalopathy and epilepsy - Dong, Meng; Zhang, Tianyu; Hu, Ruimei; Li, Meng; Wang, Guan; Liu, Xinjie (Frontiers in Pediatrics, 2022)
Objective: STXBP1 mutations are associated with early onset epileptic encephalopathy (EOEE). Our aim was to explore the phenotype spectrum, clinical treatment and prognosis of STXBP1-related encephalopathy (STXBP1-E). Methods: Clinical and genetic data were collected from 10 patients with STXBP1 mutations. These patients were examined and diagnosed from 2015 to 2021 at the Pediatric Department of Qilu Hospital. Blood samples were collected and sequenced by next generation sequencing and Candidate pathogenic variants were identified using Sanger sequencing in all family members. Results: All of the patients showed severe epilepsy, varying degrees of intellectual disability and delayed motor. The patients developed multiple seizure types and abnormal EEG results at onset, and focal seizures were the most frequent seizure type. Among the patients, 2 were diagnosed with Ohtahara syndrome, 2 patient was diagnosed with West syndrome. The other 6 patients could not be diagnosed with any specifically recognized epilepsy syndrome. 5 of the 10 patients had a history of fever with seizures, 4 of whom had eliminated intracranial infection according to the results of cerebrospinal fluid (CSF) examinations, and the other patient was diagnosed with anti-MOG-associated encephalitis. We identified one patient with a complete deletion of STXBP1 and 9 patients with de novo heterozygous mutations of STXBP1. Among those mutations, 4 were novel (c.560C>T, c.1315A>T, c.751G>C, and c.554_559del), and 5 had been previously reported (c.364C> T, c.569G>A [2 cases], c.748C>T, and c.1651C>T). For 8 of our patients, different combinations of AEDs led to seizure freedom. 1 patient with MOG antibodies in his serum obtained a poor therapeutic effect from the traditional AEDs treatment, so he had to achieve seizure-free status through VNS, which had little effect on his psychomotor ability. Fortunately, in one case, patient psychomotor ability was improved through VNS. Conclusion: Our study shows that STXBP1 screening should be considered in patients with neonatal seizures with intellectual disability, and frequent seizures with fever should also be considered with the STXBP1 mutation when intracranial infection is eliminated. VNS has expanded outcome measures to include behavioral and developmental function as well as seizure control.